Tungiasis infestation in Tanzania - Humphrey D. Mazigo; Emmanuel Behamana; Maria Zinga; Jorg Heukelbach (Journal of Infection in Developing Countries)
Tungiasis is caused by the jigger flea Tunga penetrans. We describe a case of severe infestation from Kigoma region, Western Tanzania. A 19-year-old male with epilepsy and mental disability presented with ulcerated and inflamed toes. Clinical examination revealed the presence of approximately 810 embedded jigger fleas on the feet, and another 60 lesions on the hands. The patient presented with fissures on the feet, hands and soles. He had difficulty walking and erythematous, oedematous, ulcerated and inflamed skin around the feet. Living conditions were precarious. The patient was assisted to extract the embedded fleas and his feet were washed with disinfectants. Oral antibiotics were given. The case shows that the disease may reach high parasite loads in Tanzanian individuals, with consequently severe pathology. There have been single reports of returning tourists from Tanzania with tungiasis, but the epidemiological situation and the geographic occurrence of the disease in this country are not known. Systematic studies are needed to increase knowledge on the epidemiological situation of tungasis in Tanzania and to identify endemic areas.